Users Choice of Social Media Websites -A Study of The Shimla City of Himachal Pradesh - Parmar, Jai Singh (Gyan Management Journal, 2011)
The internet access at present, with its unique advantage has become most popular and undoubtedly the communication medium of the future. The marketers around the world are striving hard to reach their target audience through various media. The usage of the internet is highest among the young audiences belonging to the larger towns and every business is using the internet to achieve the competitive advantage of capturing customer's interests in buying by the web. The business environment in recent times is characterized by the social media and each and every customer are going towards social media. Therefore, the shining businesses has no other options. In order to adapt this new culture change on the ongoing way of communicating and where the bloggers are free to state what t'hey want, the social media services such as Twitter, Facebook, Orkut, Linkedln and many other websites have a great impact on the millions of people especially those under the age of 35, who interacts with each other and view the different brands. In this study, an attempt has been made to examine the user's choice and preferences of the social media in and around Shim/a city of Himachal Pradesh.
Keywords: Social networking; internet; Users choice; Online advertising; Digital brands; trategic orientation; Selfefficacy; Users Generated Content{UGC)